Law beyond Israel from the Bible to the Qur'an - Zellentin, Holger Michael 1976- (Oxford Oxford University Press, 2022)
The Hebrew Bible formulates two sets of law: one for the Israelites and one for the gentile “residents” living in the Holy Land. Law Beyond Israel: From the Bible to the Qur’an argues that these biblical laws for non-Israelites form the historical basis of qur’anic law. The study corroborates its central claim by assessing laws for gentiles in late antique Jewish and especially in Christian legal discourse, pointing to previously underappreciated legal continuity from the Hebrew Bible to the New Testament and from late antique Christianity to nascent Islam. This volume first sketches the legal obligations that the Hebrew Bible imposes on humanity more broadly and, more specifically, on the non-Israelite residents of the Holy Land. It then traces these laws through Second Temple Judaism to the early Jesus movement, illustrating how the biblical laws for residents inform those formulated in the Acts of the Apostles. Building on this legal continuity, the study employs detailed historical and literary analyses of legal narratives in order to make three propositions. First, rabbinic laws for gentiles, the so-called Noahide Laws, while offering a more lenient interpretation than the one we find in Acts, are equally based on the biblical laws for gentile residents of the Holy Land. Second, Christians generally appreciated and even expanded the gentile laws of Acts. Third, the Qur’an remakes traditional Arabian religious practice by formulating its own distinctive approach to the biblical laws for gentiles, in close continuity with—and at times in critical distance from—late antique Jewish and especially Christian gentile law
English
Keywords: Comparative Religion; History of religion